Tibial Tubercle Anteromedialization Using the Multi-Directional Tibial Tubercle Transfer System - Anna Bartsch MD; Ran Atzmon MD; Kinsley Pierre BS; Monica S. Vel BS; Seth L. Sherman MD (SAGE Publishing, 2024)
Background: Tibial tubercle osteotomy (TTO) can realign the patellofemoral joint and reduce patellofemoral contact stress. Anteriorization can reduce compressive patellofemoral loads and medialization shifts the pulling direction on the patella, thereby lowering the load on the lateral compartments. Indications: Patellofemoral instability, patellofemoral malalignment, and distal and lateral chondral defects. Technique Description: The Multi-Directional Tibial Tubercle Transfer System (MD3T) uses a generic 3-dimensional cutting template to create 2 compound wedges that are individually transposed and adjusted to achieve multiplanar correction. For isolated tibial tubercle anteriorization , the primary wedge is solely used and the proximal bone defect is filled with autograft taken from the distal part of the wedge and synthetic bone graft substitution. For tibial tubercle medialization , the primary and secondary wedges are transposed, filling each other's respective spaces. Through the transposition of the primary and secondary wedges, partial filling of the defect with the patient's own bone is achieved, reducing the bone defect. For combined anteromedialization , both of these techniques are merged. Results: During walking fatigue test and chair rising test in a cadaveric simulated 42-day healing period, no loosening or cracking occurred. Clinical study results on this technique are pending. Conclusion: The MD3T system achieves with its wedge technique a precise and reproducible multiplanar correction in TTO. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.